Lost in translation: reproductive health care experiences of Somali Bantu women in Hartford, Connecticut. - Gurnah, Khadija; Khoshnood, Kaveh; Bradley, Elizabeth; Yuan, Christina (Journal of midwifery & women's health, 2011)
Reproductive health problems are the leading cause of women's morbidity and mortality worldwide. In the United States, officially sponsored refugee women continue to face challenges in accessing reproductive health programs despite having access to health insurance.
Keywords: Adult; Attitude to Health; Communication Barriers; Connecticut; Cultural Characteristics; Female; Focus Groups; Health Services Needs and Demand; Health Status; Humans; Nursing Methodology Research; Socioeconomic Factors; Somalia; Vulnerable Populations; Women's Health; Young Adult